2017
DOI: 10.1002/admi.201700506
|View full text |Cite
|
Sign up to set email alerts
|

Mussel‐Inspired Polyesters with Aliphatic Pendant Groups Demonstrate the Importance of Hydrophobicity in Underwater Adhesion

Abstract: In addition to DOPA, several other residues including lysine, tryptophan, histidine, arginine and phosphorylated serine are proposed to play key roles in adhesion of mussels and other underwater organisms. [5] In preparing synthetic mimics of mussel adhesives, incorporating DOPA or other hydrophilic moieties is a common theme with the aim that such moieties can potentially outcompete interactions of water with the surface. [6] Interestingly, the role of hydrophobic groups to drive water away has not been expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 44 publications
1
89
0
Order By: Relevance
“…The CFPs are also capable of the adhesion at wet or underwater situations, although the bonding strength is much lower because of the formation of hydrated cation layers. [ 17 ] White and Wilker [ 18 ] and Joy and co‐workers [ 19,20 ] incorporated monomers with electrostatic charges or aliphatic pendants into CFPs, achieving underwater bonding strength of 0.4 MPa on aluminum and 0.65 MPa on glass, respectively. By adjusting the polarity [ 21 ] or the hydrophilicity [ 22 ] of CFP backbones, Wan et al reported improved bonding strength of 1.13 and 1.33 MPa on glass substrates.…”
Section: Methodsmentioning
confidence: 99%
“…The CFPs are also capable of the adhesion at wet or underwater situations, although the bonding strength is much lower because of the formation of hydrated cation layers. [ 17 ] White and Wilker [ 18 ] and Joy and co‐workers [ 19,20 ] incorporated monomers with electrostatic charges or aliphatic pendants into CFPs, achieving underwater bonding strength of 0.4 MPa on aluminum and 0.65 MPa on glass, respectively. By adjusting the polarity [ 21 ] or the hydrophilicity [ 22 ] of CFP backbones, Wan et al reported improved bonding strength of 1.13 and 1.33 MPa on glass substrates.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported recently that a hydrophilic adhesive with catechol does not adhere underwater compared to a relatively hydrophobic adhesive without catechol groups. 49 Therefore, for effective underwater adhesion, initially the polymer should make interfacial contact with the surface and remove bound water, which in this case is achieved by a conformable hydrophobic adhesive. Also, polar functional groups with strong interfacial interactions are essential to display significant adhesion underwater.…”
Section: Results and Discussionmentioning
confidence: 99%
“…21,22 In order to overcome such difficulties, synthetic wet adhesives emulating natural adhesive materials of marine organisms have been extensively investigated. 23 Representative examples include wet adhesives mimicking the proteins present in biological system such as mussel adhesives, [23][24][25][26] barnacle cements, 27 and sandcastle-worm glues. 28 These marine organism-inspired synthetic wet adhesives typically have the use of 3,4-dihydroxyphenylalanine (DOPA) in common, and many different types of DOPA-based wet adhesives have demonstrated effective wet adhesion performance.…”
Section: Introductionmentioning
confidence: 99%